Empirical Effects of Price, User Experience, and Peer Influence on Goal-Oriented Browsing in Indonesian Online Food Shopping - Widarto Rachbini (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: Within the continuously evolving landscape of the online food shopping industry, there is a recognized urgency for enhanced user experiences, novel pricing strategies, and sophisticated marketing approaches. These elements are integral to captivating and retaining customers within the fiercely competitive digital marketplace.Purpose: This study investigates the behaviors of Indonesian consumers within the realm of online food purchases, driven by the imperative to unravel pivotal factors influencing their decision-making processes. Design/methodology/approach: Employing a quantitative approach and structural equation modeling (SEM), this research rigorously examines the influence of price-awareness, user experience, and peer influence on both goal-oriented browsing and persuasion efficacy among Indonesian consumers. Findings/Result: The study found that price-awareness and user experience significantly influence goal-oriented browsing. Peer influence significantly affects both goal-oriented browsing and persuasion efficacy. Goal-oriented browsing positively impacts persuasion efficacy.Conclusion: The study concludes that enhancing user experience, leveraging peer influence, and adopting competitive pricing are essential for engaging and persuading consumers. Strategic improvements in these areas not only enhance persuasion efficacy but also solidify competitive positions within the market landscape.Originality/value (State of the art): This study uniquely examines the combined effects of price-awareness, user experience, and peer influence on goal-oriented browsing and persuasion efficacy in Indonesian online food shopping. It offers valuable insights and actionable strategies for marketers, contributing to advanced knowledge in digital marketing and consumer behavior. Keywords: price-awareness, user experience, peer influence, goal-oriented browsing, persuasion efficacy.